Freeze-thaw durability and shear responses of cemented slope soil treated by microbial induced carbonate precipitation - Gowthaman, Sivakumar; Nakashima, Kazunori; Kawasaki, Satoru (Soils and foundations, 2020)
Instability of slope soils under varying nature is one of the serious concerns in geotechnical engineering. Microbial induced carbonate precipitation (MICP) is a recently emerged, biological ground improvement technique, and that has the potential to enhance the shear strength, modify the surface conditions and promote the stability of deposits. This paper presents the experimental works conducted to investigate the durability and shear responses of MICP treated slope soil, demonstrating the feasibility of technique as potential alternative for slope soil stabilization. The first objective is to investigate the freeze–thaw (FT) response of MICP specimens, because FT cycles can affect the aggregate stability in regions with seasonal frost, which in turn impacts runoff and erosion in slopes. FT tests were performed as a credible indicator of durability, and the subjected specimens were monitored nondestructively (mass loss, S-wave, P-wave velocities). Secondly, shear tests were performed, and effective strength properties were analyzed at peak and residual states. FT test results suggest that contact cementation provides additional resistive forces in slope soil against progressive expansion of pore water during FT; however, aggregate stability is attributed to adequate cementation level which facilitates effective particle contacts. Shear test results indicate that MICP has influence on friction and cohesion parameters. However, the residual strength is mainly contributed by friction angle, only a minor effect from cohesion.